The Reality of the Administrative Empowerment of Secondary School Principals and its Relation to Some Variables "Field Study in Lattakia Governorate" - Mansour , Smaia; Wazzan, Rawan (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The study aims to identify the reality of administrative empowerment among secondary school principals in Lattakia Governorate according to its dimensions (delegation of powers, teamwork, decision making, support and support), and study the differences between managers in the reality of administrative empowerment (sub dimensions and scale as a whole) Years of experience in administrative work, scientific qualification. The research was based on a descriptive analytical method. A questionnaire was developed and distributed to a sample of (152) managers and managers, of which (138) were complete and valid for statistical analysis, with a response rate of 90.79%. Using the appropriate statistical methods, the most important research results were: Secondary school principals in Lattakia governorate have generally good administrative capacity, and sub-dimensions: delegation of authority, teamwork, decision making, support and support. The gender variable does not affect the degree of administrative empowerment of secondary school principals in Lattakia governorate, where there were no statistically significant differences between the average managers and managers in the general administrative empowerment situation. As for the subdivisions, there was a difference in support, Decision in favor of males. The degree of administrative empowerment of secondary school principals in Lattakia governorate has increased with the number of years of experience and scientific qualification. There were statistically significant differences between the averages of the degrees of managers according to the variables of years of experience in administrative work and the scientific qualifications. And for the qualification of graduate studies, at the level of sub-dimensions, and the scale as a whole.